Excitonic mobility edge and ultra-short photoluminescence decay time in n-type GaAsN - Eßer, F.; Winner, S.; Patanè, Amalia; Helm, M.; Schneider, H. (American Institute of Physics, 2016)
We use time-resolved photoluminescence (PL) spectroscopy to study the recombination dynamics in Si-doped GaAsN semiconductor alloys with a nitrogen content up to 0.2%. The PL decay is predominantly monoexponential and exhibits a strong energy dispersion. We find ultra-short decay times on the high-energy side and long decay times on the low-energy side of the photoluminescence spectrum. This asymmetry can be explained by the existence of an additional non-radiative energy transfer channel and is consistent with previous studies on intrinsic GaAsN epilayers. However, the determined maximum decay times of GaAsN:Si are significantly reduced in comparison to undoped GaAsN. The determined excitonic mobility edge energy constantly decreases with an increase in the N content, in agreement with the two-level band anticrossing model.